Do needle characteristics of Pinus uncinata depend on climatic factors? - Boratyńska, Krystyna; Muchewicz, Ewelina (Biodiversity: Research and Conservation, 2006)
Samples of 10 previous-year needles each were collected from 30 individuals of Pinus uncinata in the Vall de Ransol (Pyrenees) in 1999, 2000 and 2003. Each needle was analysed separately for 15 characters. The dependence of average values of particular needle characters in the particular year on average monthly temperatures, average annual temperature, average temperature in June-September, the number of days with average temperatures > 10 oC per year, annual precipitation and precipitation in June-September were tested. Results of the preliminary analyses suggest that numbers of stomata, stomatal rows and resin canals in needles can be determined by temperature and precipitation regimes of the year of initiation of the needle (i.e. bud formation), while needle dimensions can be influenced by the temperatures and precipitation in the year of their development and intensive growth.